Memaksimalkan Kepribadian Kritis Positif Materi Sifat Gereja (Satu) Model PBL Fase F SMK Theresiana Semarang - Y Dwi Astanto (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This study aims to maximize the positive critical personality of eleventh-grade Culinary 2 students at SMK Theresiana Semarang through the PBL Phase F model on the Church Nature material. The research background reflects the complexity of educational challenges in Indonesia, focusing on academic issues and educational access disparities. A Center of Excellence School such as SMK Theresiana Semarang strives to address these challenges through the Merdeka Curriculum and a vocational education approach based on Christian values.The exploration of the causes of the problem highlights the cognitive, affective, and psychomotor aspects of students. Self-concept understanding is influenced by internal and external factors, while the affective aspect, especially self-acceptance and meaningful life, affects motivation and self-confidence. Psychomotor challenges, such as reluctance to speak in public, are also related to a lack of strong self-acceptance.Recommendations for improvement involve a holistic approach, including emotional support, inclusive learning, wise social media management, and effective guidance. Improving self-acceptance is directed towards building a positive identity, stable self-esteem, and meaningful life motivation. These steps are expected to contribute positively to the critical personality development of students, creating an inclusive and empowering learning environment at SMK Theresiana Semarang.